PARADIGMA FILSAFAT PENDIDIKAN ISLAM DALAM MEMBANGUN KESADARAN EKOTEOLOGIS PESERTA DIDIK - Achmad Musthofa; Dwy Anggra; Yahya Husein Al-Azhari; Febry Suprapto (PARADIGMA: JURNAL PEMIKIRAN DAN PENELITIAN PENDIDIKAN, 2025)
This study aims to examine the paradigm of Islamic educational philosophy in fostering students’ ecotheological consciousness through an integrative conceptual framework that links the ontological, epistemological, and axiological dimensions of Islamic education. Education is frequently positioned as a primary instrument for responding to the ecological crisis; however, the dominant educational paradigms to date still demonstrate fundamental limitations in cultivating transformative ecological awareness. This research adopts a qualitative approach using an integrative literature review design that is conceptual and critical in nature. The data sources consist of reputable scholarly literature, including journal articles indexed in SCOPUS and the Web of Science, nationally accredited SINTA journals, as well as relevant academic books and handbooks. Data analysis was conducted through thematic and philosophical analysis, involving stages of concept coding, thematic categorisation, comparative analysis, and conceptual synthesis. The findings indicate that an ecotheological perspective within the philosophy of Islamic education possesses significant theoretical and practical relevance in the global discourse on sustainable education. Moreover, the study demonstrates that Islamic educational philosophy provides a comprehensive conceptual framework for developing students’ ecotheological consciousness through the integration of ontological, epistemological, and axiological dimension